2017
DOI: 10.1101/202986
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cardio- and neurometabolic effects of lower-body pressure-supported exercise in obese non-diabetic women: Resetting autonomic imbalance?

Abstract: Background: Overnutrition and underactivity cause most chronic disease via

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Also, naloxone (a drug that antagonises opioid effects by competing for opiate receptor sites in the central nervous system) inhibited the effects of oxytocin on the stress hormone response in the aforementioned exercise testing study, suggesting that oxytocin mediates its effects through the release of endogenous opioids. In support of this hypothesis, endogenous plasma oxytocin concentrations were highly correlated with plasma levels of β-endorphin (127). Of interest, orexin-A, which is positively associated with the amount of spontaneous physical activity (132), also showed remarkable positive correlation with plasma oxytocin (127,132).…”
Section: Oxytocin System In Weight Loss and Exercisementioning
confidence: 63%
See 3 more Smart Citations
“…Also, naloxone (a drug that antagonises opioid effects by competing for opiate receptor sites in the central nervous system) inhibited the effects of oxytocin on the stress hormone response in the aforementioned exercise testing study, suggesting that oxytocin mediates its effects through the release of endogenous opioids. In support of this hypothesis, endogenous plasma oxytocin concentrations were highly correlated with plasma levels of β-endorphin (127). Of interest, orexin-A, which is positively associated with the amount of spontaneous physical activity (132), also showed remarkable positive correlation with plasma oxytocin (127,132).…”
Section: Oxytocin System In Weight Loss and Exercisementioning
confidence: 63%
“…In support of this hypothesis, endogenous plasma oxytocin concentrations were highly correlated with plasma levels of β-endorphin (127). Of interest, orexin-A, which is positively associated with the amount of spontaneous physical activity (132), also showed remarkable positive correlation with plasma oxytocin (127,132).…”
Section: Oxytocin System In Weight Loss and Exercisementioning
confidence: 63%
See 2 more Smart Citations
“…It was determined that the pOT concentrations did not change in either the early follicular phase or the midluteal phase of the menstrual cycle [23]. Another study reported that 11 weeks of lower-body pressure supported exercise, which was applied to obese non-diabetic women aged 18-56 years by use of 60% body weight for half an hour 2-3 times a week, had no effect on pOT concentrations [24]. When the effects of a maximum fatigue test, 60-minute treadmill and a 56-km ultramarathon, were evaluated among seven runners (five males and two females), the ultramarathon was found to be the only running exercise that caused a significant increase in pOT value [25].…”
Section: Discussionmentioning
confidence: 99%